Using 50 K Single Nucleotide Polymorphisms to Elucidate Genomic Architecture of Line 1 Hereford Cattle - Huang, Yijian; Maltecca, Christian; MacNeil, Michael D.; Alexander, Lee J.; Snelling, Warren; Cassady, Joseph P. (Frontiers in Genetics, 2012)
Hereford is a major beef breed in the USA, and a sub-population, known as Line 1 (L1), was established in 1934 using two paternal half-sib bulls and 50 unrelated females. L1 has since been maintained as a closed population and selected for growth to 1 year of age. Objectives were to characterize the molecular genetic architecture of L1 (n = 240) by comparing a cross-section of L1 with the general US. Hereford population (AHA, n = 311), estimating effects of imposed selection within L1 based on allele frequencies at 50 K SNP loci, and examining loci-specific effects of heterozygosity on the selection criterion. Animals were genotyped using the Illumina BovineSNP50 Beadchip, and SNP were mapped to UMD3.0 assembly of the bovine genome sequence. Average linkage disequilibrium (LD), measured by square of Pearson correlation, of adjacent SNP was 0.36 and 0.16 in L1 and AHA, respectively. Difference in LD between L1 and AHA decreased as SNP spacing increased. Persistence of phase between L1 and AHA decreased from 0.45 to 0.14 as SNP spacing increased from 50 to 5,000 kb. Extended haplotype homozygosity was greater in L1 than in AHA for 95.6% of the SNP. Knowledge of selection applied to L1 facilitated a novel approach to QTL discovery. Minor allele frequency was (FDR < 0.01) affected by cumulative selection differential at 191 out of 25,901 SNP. With the FDR relaxed to 0.05, 13 regions on BTA2, 5, 6, 9, 11, 14, 15, 18, 23, and 26 are co-located with previously identified QTL for growth. After adjustment of postweaning gain phenotypes for fixed effects and direct additive genetic effects, regression of residuals on genome-wide heterozygosity was −235.3 ± 91.6 kg. However, no SNP-specific loci where heterozygotes were significantly superior to the average of homozygotes were revealed (FDR ≥ 0.17). In conclusion, genome-wide SNP genotypes clarified effects of selection and inbreeding within L1 and differences in genomic architecture between the population segment L1 and the AHA population.